A qualitative study of barriers and opportunities for concussion communication and management among parents of youth sports athletes. (July 2019) - Sarmiento, Kelly; Donnell, Zoe; Bell, Elizabeth; Tennant, Bethany; Hoffman, Rosanne
Background: Concussion, a commonly reported injury among young athletes, can lead to short- and long-term physical, cognitive, emotional, and sleep-related symptoms. Parents are in a unique position to help identify a possible concussion and to support an athlete's recovery. Methods: This qualitative study used a focus group methodology to explore five research questions focused on two main topics: (1) parents' perception of concussion and (2) parent–athlete communication. Two authors independently reviewed notes from each of the focus groups and then generated a list of emerging themes related to five research questions. Results: Parents in this study valued and were interested in discussing concussion with their athletes. However, parents were uncertain about their role in promoting concussion safety and often rely on coaches to communicate with athletes about concussion reporting and recovery. Participants described barriers their athletes may face in concussion reporting and suggested strategies to improve communication about both reporting and recovery. Conclusion: Concussion education efforts may benefit from promoting specific actions parents can take to prevent concussion and how to communicate effectively with their child about reporting a possible concussion.